10 kV SiC MOSFET based medium voltage power conditioning system for asynchronous microgrids - Chen, Ruirui (2023)
Distributed energy resources (DERs) and microgrids have seen tremendous growth and research activities in recent years. Flexible DERs and asynchronous microgrids (ASMG) can have many system-level benefits over fixed DERs and conventional microgrids. The key enabler for flexible DERs and ASMG is a power converter based power conditioning system (PCS) as the interface between DERs/microgrids and the medium voltage (MV) distribution grid. High voltage (HV, >3.3 kV) silicon carbide (SiC) based MV converter is now a promising solution for the PCS. This article presents development and testing of a 10 kV SiC MOSFET based MV PCS for 13.8 kV ASMG. MV PCS converter design addressing high dv/dt issue generated by fast switching of the 10 kV SiC MOSFET is presented. The developed PCS is successfully tested at 25 kV dc 13.8 kV ac voltages and 100 kVA power. Grid support functions are also demonstrated with the developed PCS prototype and hardware tests beds, validating HV SiC converter benefits for ASMG.